PEMIKIRAN PENDIDIKAN ISLAM: KONSEP, TUJUAN, DAN RELEVANSINYA DI ERA MODERN - Hamida Olfah (CV. ADIBA AISHA AMIRA, 2026)
Islamic education represents an educational system that emphasizes the balanced development of intellectual, spiritual, and moral dimensions in shaping individuals who are knowledgeable, faithful, and possess noble character. This study aims to analyze the fundamental concepts of Islamic education, examine its educational objectives, explore the educational thoughts of prominent Muslim scholars, and explain their relevance in addressing contemporary challenges as well as their contribution to the process of village regulation drafting and legal drafting practices. The study employs a library research method by utilizing scholarly books, academic journals, scientific articles, and relevant research findings. Data were analyzed using a descriptive-analytical approach to provide a comprehensive understanding of the evolution of Islamic educational thought from classical to contemporary periods. The findings reveal that Islamic education is founded upon three essential concepts: tarbiyah, ta'lim, and ta'dib, which collectively promote the holistic development of human potential. The ultimate objective of Islamic education is the formation of insan kamil (the complete human being) characterized by the integration of knowledge, faith, and morality. The educational perspectives of Al-Ghazali, Ibn Sina, HAMKA, and Azyumardi Azra demonstrate that Islamic educational thought remains highly relevant in responding to globalization, digital transformation, and moral challenges. Furthermore, Islamic values such as trustworthiness, justice, deliberation, and responsibility provide important ethical foundations for village regulation drafting oriented toward public welfare.